CMET-07. FRAILTY PREDICTS MORTALITY AFTER RESECTION OF BRAIN METASTASES. (5th November 2018) - Gupta, Saksham; Bi, Wenya Linda; Larsen, Alexandra Giantini; Dawood, Hassan; Fandino, Luis; Smith, Timothy R; Aizer, Ayal; Dunn, Ian F
Abstract: INTRODUCTION: Brain metastases are the most common type of brain tumor, though determining candidates for resection may be challenging. Patients' unfavorable prognoses make pre-operative risk stratification critical in the selection of patients that are likely to benefit from resection. METHODS: Multivariable logistic regression was applied to 3, 532 cases of secondary neoplasms of the brain in the American College of Surgeons National Surgical Quality Improvement Program database. The validated 5-criteria modified frailty index (mFI-5) score was utilized to quantify frailty, characterized as an mFI-5 score of 2 or higher. RESULTS: The median age in the cohort was 61 years, and the majority of patients were female (55%). Frailty was present in 17% of patients. The most frequent 30-day post-operative medical complications were venous thromboembolism (3.1%), pneumonia (2.7%), and urinary tract infections (2.2%). Unplanned readmissions and reoperations occurred in 12.2% of patients and 4.9% of patients, respectively. The incidence of death was 4.2% across the cohort, including 1.2% during index hospitalization. Frailty was associated with pneumonia (OR 2.7, p DISCUSSION: Frailty was associated with post-operative medical complications and death, in particular during the post-discharge phase. Frailty should be used in risk-stratifying patients.